STRUCTURAL AND DYNAMIC STUDIES OF DELTA-BI2O3 OXIDE ION CONDUCTORS .4. AN EXAFS INVESTIGATION OF (BI2O3)1-X(M2O3)X FOR M = Y, ER, AND YB - Battle, P; Catlow, C; Chadwick, A; Cox, P; Greaves, G; Moroney, L (1987)
The local structural environments of Bi3+ and dopant cations in the fluorite-structured solid solutions (M2O3)x(Bi2O3)1-x (M = Y, Er, Yb) have been studied using extended X-ray absorption fine structure techniques. The results show that the BiO shell is heavily disordered with an asymmetric radial distribution function. The Bi3+ ion tends to be displaced from its centrosymmetric, cube center site. The first coordination shell of the dopant is comparatively ordered. Varying the dopant cation has a small effect on the local structural environment and increasing the dopant concentration causes a small increase in the degree of local order. Data obtained over a range of temperatures show that the large anisotropy in the BiO shell is attributable to static displacements from the perfect lattice sites. The degree of correlation between the thermal vibrations of the anion sublattice and those of the Bi atoms differs from that observed between those of the anion sublattice and the dopant atoms; the significance of this for ionic conductivity is discussed. © 1987.